Challenging the Normative Truth Logic in the Politics of Apology: A Quest for Recognition. (6th September 2018) - De Wilde, Lieselot; Roets, Griet; Vanobbergen, Bruno
Abstract: In recent years, the historical abuse perpetrated against children in residential child-welfare and protection services has increasingly been perceived as a public concern. In the context of this European and global development, several formal inquiries commissioned by authorities into the alleged historical abuse of children in social work services were perceived as a political priority to repair human injustices, and were set up as an attempt to come to terms with the failure of social welfare policies and services in the past. The number of official public apologies has continued to increase since the turn of the century. In this article, we radically question the normative truth logic that is at stake in these politics of apology as a way to give recognition on both an individual and a collective level, and argue that social work needs to critically deal with its own confusing history, with which it is interwoven, to be able to clarify what contemporary social work represents.